Public funding and corporate innovation - Mathias Beck; Martin Junge; Ulrich Kaiser (ETH Zurich, KOF Swiss Economic Institute, 2018)
We review and condense the body of literature on the economic returns of public R&D on private R&D and find that: (i) private returns to R&D appear to be large and larger than the returns to alternative investments; (ii) private R&D and R&D subsidies are positively correlated and there is no evidence for crowding out; (iii) R&D cooperation increases private R&D; (iv) there appear to exist complementarities between alternative sources of funding; (v) the mobility of R&D workers, particularly of university scientists, is positively related to innovation; (vi) there are many university spin-offs but these are no more successful than non-university spin-offs; (vii) universities constitute important collaboration partners and (viii) clusters enhance collaboration, patents and productivity. Key problems for economic policy advice are that the identification of causal effects is problematic in most studies and that little is known about the optimal design of policy measures.
Keywords: C54; J6; I28; O3; L52; 330; R&D subsidies; R&D tax credits; cooperation; labor mobility; returns to R&D; university spin-offs; R&D clusters; public-private knowledge transfer